Czytanie audiowizualności. O literaturze w cyberprzestrzeni - Dorak-Wojakowska, Lilianna (Przestrzenie Teorii, 2015)
A review of the book entitled Literature – new media. Homo irretitus in the literary culture of the 20th and 21st centuries (Literatura – nowe media. Homo irretitus w kulturze literackiej XX i XXI wieku) deals with the clash between literature and new media. The book constitutes an academic guide to the world of intermedia narration and cyber-literature. It may serve students, teachers and form tutors as a source of additional knowledge on the convergence of media. The authors reflect widely upon the transformation of both literary creation and the theory dealing with the art of language, as well as upon the changes in the study of literature, books and reading in the 21st century.